Advancing Sukuk Markets: Legal Frameworks, Regulatory Developments, and Default Challenges in Malaysia and the United Arab Emirates - Abdullah, Ziarmal; Humaidi, Muchtim (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: This study examines recent developments and key challenges in the sukuk markets of Malaysia and the United Arab Emirates (UAE), with a focus on legal, regulatory, and post-default frameworks. It analyzes the institutional structures that shape sukuk issuance in both countries. Research Methods: Using a qualitative approach, the research draws on academic literature, official reports, news articles, and other relevant sources. It also outlines fundamental sukuk theories, instruments, and global market issues. Results: The findings indicate that both countries have made notable progress in advancing socially responsible sukuk and regulatory initiatives. However, the UAE faces challenges such as the absence of standardized legal frameworks and independent rating agencies. Malaysia, while leading globally in sukuk issuance, continues to encounter difficulties aligning its regulations with international standards. Conclusion: The study recommends greater standardization, increased sukuk issuance, and more transparent post-default mechanisms to support the long-term development of sukuk markets.